Primary Signet Ring Cell Adenocarcinoma of the Urinary Bladder: A Report of 2 Cases() - Boukettaya, Wiem (Urol Case Rep, 2014)
Primary signet ring cell carcinoma of the urinary bladder is a rare and aggressive histologic subtype of adenocarcinoma. In general, this tumor occurs in the middle age, and clinical presentation does not differ from transitional cell carcinomas. The prognosis is often poor, given the advanced stage at diagnosis. To our knowledge, <100 cases of signet ring cell adenocarcinoma of the urinary bladder have been reported. We report 2 cases with bladder linitis plastica primitive, and we draw attention to its pathologic, anatomoclinical, and evolution specificity to optimize its therapeutic management.